2002
DOI: 10.1002/jclp.1155
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits and pathology in older and younger incarcerated women

Abstract: Personality disorders were examined in 157 incarcerated women, using the Schedule for Nonadaptive and Adaptive Personality (SNAP; Clark, 1996) to assess 10 Diagnostic and Statistical Manual of Mental Disorders, Third Edition, Revised (DSM-III-R; American Psychiatric Association, 1987) diagnostic categories and dimensions and 15 domains of trait/temperament relevant to disordered personality. Similar to both community samples and incarcerated men, older women had lower rates of personality disorders than younge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…SEM analyses showed that significant predictors of the Externalizing factor were gender (men had higher means on the latent variable), age (an inverse association), greater exposure to trauma, and exposure to combat trauma, specifically. This is consistent with prior research on the association between gender (Kramer, Krueger, & Hicks, 2008), age (Hurt & Oltmanns, 2002; Littlefield, Sher, & Wood, 2009) and externalizing psychopathology. The specificity of the relationship between combat exposure and externalizing was unexpected, however, and may be a function of the large percentage of male veterans in this sample.…”
Section: Discussionsupporting
confidence: 91%
“…SEM analyses showed that significant predictors of the Externalizing factor were gender (men had higher means on the latent variable), age (an inverse association), greater exposure to trauma, and exposure to combat trauma, specifically. This is consistent with prior research on the association between gender (Kramer, Krueger, & Hicks, 2008), age (Hurt & Oltmanns, 2002; Littlefield, Sher, & Wood, 2009) and externalizing psychopathology. The specificity of the relationship between combat exposure and externalizing was unexpected, however, and may be a function of the large percentage of male veterans in this sample.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with previous studies in which younger individuals showed higher rates of impulsive and sensation-seeking behavior than older individuals (Hurt & Oltmanns, 2002;Todesco, 2004).…”
Section: Impulsivity Among Incarcerated Womensupporting
confidence: 94%
“…Impulsivity is an important component of borderline and antisocial personality disorders (Casillas & Clark, 2002;Coles, 1997;Hochhausen et al, 2002;Hurt & Oltmanns, 2002). Therefore, we expected to find a significant relationship between these disorders and impulsivity.…”
Section: Impulsivity and Personality Disordersmentioning
confidence: 96%
“…A national rate of mental illness for incarcerated women has been estimated at 73% of all female state prisoners and 61% of federal prisoners (Bureau of Justice Statistics, 2006). Current national data could not be found regarding the rates of mental illness in incarcerated women by specific categories but Hurt and Oltmanns (2002) found that 64% of the women prisoners they studied met the criteria for at least one personality disorder.…”
Section: Demographicsmentioning
confidence: 78%